STRUCTURAL ELEMENTS AND STYLISTIC ASPECTS IN THE THIRD SYMPHONY “SEMNE” BY CORNEL ȚĂRANU - Cristian BENCE-MUK (Studia Universitatis Babeş-Bolyai. Musica, 2025)
The article explores The Third Symphony “Semne” (Signs) by Romanian composer Cornel Țăranu, a pivotal work composed in 1984 that marks a stylistic shift in his symphonic output. Known for his deep connection to Enescu’s musical legacy and a commitment to compositional innovation, Țăranu transitions in this piece from a constructivist style to a more expressive, synthesized language. The symphony is structured as a monopartite sonata form, featuring a distinctive brass “signal-theme” (Theme A) and a lament-like secondary theme (Theme B), rooted in Romanian folk idioms. Its development section is richly varied, highlighting pointillism, stretto, melodic expansions, and inverted counterpoint. The work concludes with a cathartic coda evoking collective lament. Analytical comparisons are drawn with Țăranu’s other symphonies and orchestral works, illustrating stylistic continuity and thematic evolution. The article underscores the symphony’s central place in his oeuvre and its symbolic significance within Romanian contemporary music.